KETERKAITAN PENDIDIKAN, PERUBAHAN SOSIAL BUDAYA, MODERNISASI DAN PEMBANGUNAN - Adelina Yuristia (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2017)
Education is one of the driving factors for the occurrence of social change and education is also one of the primary means to succeed the national development, because with education expected to print a good quality of human resources required in development, because only with pendidikanldapat do socio-cultural change,i.e. adjustment of values and attitudes that support, the development of science, changing the mindset, that supports the development and mastery of a variety of skills in the use of advanced technology to accelerate the development proces , which later by acquiring higher education and development that advance will make society more modern good lifestyle as well as his thoughts. .. Social support necessary alignment and development of education with social reality and expectations. All this shows the relationships and dependencies between different life and social institutions in the process of socio-cultural changes or the development process of a society.